2020
DOI: 10.1016/j.jaap.2020.104900
|View full text |Cite
|
Sign up to set email alerts
|

Influence of unsaturation of hydrocarbons on the characteristics and carcinogenicity of soot particles

Abstract: Highlights Increasing unsaturation increased soot size, mass, and number concentrations. Increasing unsaturation increased particle phase PAHs and soot particle carcinogenicity. Soot carcinogenicity decreased with the soot particle number. Soot carcinogenicity decreased with soot particle mass and size. Temperature increase from 1050 to 1350 °C decreased soot carcinogenicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Moreover, the rapid use of fossil-based fuel sources in recent times has been found to increase the atmosphere's harmful emissions, mainly in the form of CO2, thereby intensifying the greenhouse effect and global warming. The main challenge is to lower CO2 emissions by reducing fossil fuel reliability [6][7][8][9][10][11][12][13][14]. In another study, lower exhaust emissions were found with 50% sesame oil and 50% diesel oil blend.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the rapid use of fossil-based fuel sources in recent times has been found to increase the atmosphere's harmful emissions, mainly in the form of CO2, thereby intensifying the greenhouse effect and global warming. The main challenge is to lower CO2 emissions by reducing fossil fuel reliability [6][7][8][9][10][11][12][13][14]. In another study, lower exhaust emissions were found with 50% sesame oil and 50% diesel oil blend.…”
Section: Introductionmentioning
confidence: 99%
“…The size of soot particles typically ranges from tens to hundreds of nanometers, and such nanoparticles can penetrate the respiratory system, entering deep into the lung alveoli and being trapped in the interior [1]. Meanwhile, soot particles are known to be carriers of various species that are potentially toxic, carcinogenic, and mutagenic, such as polycyclic aromatic compounds and environmentally persistent free radicals (EPFRs) [2][3][4]. Additionally, soot plays an important role in atmospheric chemistry and global warming, through both direct radiative forcing and indirect effects on climate (e.g., by changing cloud properties) [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…The primary organic substance in soot, polycyclic aromatic hydrocarbons (PAHs), has also been linked to mutagenic and carcinogenic consequences 2 . Several past studies have described soot as a carcinogen and linked it to different kinds of cancer 8,9,10 . PM2.5 is known to cause oxidative stress and inflammation in the respiratory tract, which aggravates longterm chronic diseases like cancer and asthma as well as respiratory and cardiovascular problems 11 .…”
Section: Introductionmentioning
confidence: 99%